METODE PEMBENTUKAN MORAL UMAT PADA LEMBAGA PENDIDIKAN DAYAH DI KABUPATEN ACEH BARAT - Idris, M. Arif; Azhari, Azhari (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2022)
The existence of Dayah at West Aceh should be able to become a forum to foster the morale of people who can the behavior of the community, Education at Dayah will bring great influence to the generation and society of West Aceh. Today’s condition of the morale of society must be a concern. How can the morals of the people be shaped through Dayah education in West Aceh. So it is necessary to look at the methods used in Dayah in fostering the morale of the people. The use of descriptive research methods in researching aims of this method to make a systematic, factual, and accurate description of the facts, properties, and relationships between the phenomena under investigation. Research locations on several Dayah in West Aceh Regency with the population that is the research sample, namely Dayah educational institutions from the leadership element teungku and students. The West Aceh Dayah Education Office and the Office of the Ministry of Religious Affairs of West Aceh Regency. The results showed that moral formation is carried out through habituation, and regulations in Dayah, through ketaz'iman, and moral formation also through organizing themselves from leadership and teacher elements, where these conditions will be a reference imitated by every student and society.